"Green polyethylene" and curauá cellulose nanocrystal based nanocomposites: Effect of vegetable oils as coupling agent and processing technique. Issue 14 (11th April 2015) - Oliveira de Castro, Daniele; Frollini, Elisabete; Ruvolo‐Filho, Adhemar; Dufresne, Alain
ABSTRACT Cellulose nanocrystals (CNC) were prepared from curauá fibers via acid hydrolysis, and used as reinforcing phase for high‐density biopolyethylene (HDBPE) or green polyethylene. Castor oil (CO), epoxidized soybean oil (ESO) and epoxidized linseed oil (ELO) were chosen as compatibilizers for this study. Nanocomposites reinforced with CNC (3, 6, and 9 wt %) were processed by extrusion, using CO (3, 6, and 9 wt %) to evaluate its action as CNC dispersing agent in the HDBPE matrix. From the results obtained for these films, the CNC and oil contents were set at 3 wt%. In addition to CO, ELO, and ESO were also used, and besides processing by extrusion, extrusion/hot‐pressing process was also considered, in order to compare the two processing techniques. The nanocomposites were characterized by microscopic, thermal, mechanical, and rheological analyses. The presence of oil leads to less opaque films and improved dispersion. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1010–1019